2008
DOI: 10.1007/s11165-008-9092-y
|View full text |Cite
|
Sign up to set email alerts
|

Physics Teachers’ Perceptions of the Difficulty of Teaching Electricity

Abstract: As part of a project concerned with developing a better understanding of the detail of appropriate teaching of direct current (DC) electricity concepts, extensive individual interviews were conducted with a number of experienced senior high school physics teachers. These interviews explored teachers' perceptions of difficulties in student learning and their own teaching of DC electricity, their uses of models and analogies in this teaching, and their own understandings of the concepts of DC electricity. Eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 12 publications
0
46
0
9
Order By: Relevance
“…However, the lessons also demonstrated it is not easy for teachers to create classroom norms of inquiry and foster conceptual understanding. Demands are made with respect to classroom management and pedagogical content knowledge, encompassing the topic of electricity (Gunstone, Mulhall & McKittrick, 2009), as well as the local instruction theory and the nature of the desired classroom norms. Mr. Adler and the researcher could evaluate and adapt each lesson directly after the enactment.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, the lessons also demonstrated it is not easy for teachers to create classroom norms of inquiry and foster conceptual understanding. Demands are made with respect to classroom management and pedagogical content knowledge, encompassing the topic of electricity (Gunstone, Mulhall & McKittrick, 2009), as well as the local instruction theory and the nature of the desired classroom norms. Mr. Adler and the researcher could evaluate and adapt each lesson directly after the enactment.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…For example, the teachers here did not report using a large number of metaphors or analogies when they taught electricity. There is a lack of agreement about the best way to teach electricity, see Mulhall, McKittrick, & Gunstone (2001) and Gunstone, Mulhall, & McKittrick (2009). There is scope to explore the metaphors, analogies and models which teachers use in the classroom.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the areas which have been identified as particularly difficult for secondary school pupils and university students, and which permeate the curriculum in both sectors, are electricity energy (Halloun & Hestenes, 1985;Planinic, 2006) and forces (Halloun & Hestenes, 1985;Mualem & Eylon, 2010). These areas have also been found to be conceptually difficult for physics teachers, see for example Gunstone, Mulhall and McKittrick (2009), Halloun & Hestenes (1985) and Singh and Rosengrant (2003). Other authors have found that PGDE students can also find it difficult to reconceptualise physics topics to teach them to pupils.…”
Section: Wider Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the extensive research literature on learning DC-circuit phenomena, pupils in general have serious learning problems with understanding DC-circuit phenomena and distinguishing the main concepts from each another (Gunstone et al, 2009;McDermott & Shaffer, 1992;Shipstone et al, 1988;Duit & von Rhöneck, 1997;Millar & King, 1993). This study focuses on young pupils, whose learning of DC-circuit phenomena has not been studied to any great extent.…”
Section: Learning Problems Associated With Dc-circuit Phenomenamentioning
confidence: 99%